2012
DOI: 10.1182/blood-2011-09-377051
|View full text |Cite
|
Sign up to set email alerts
|

TCR affinity and specificity requirements for human regulatory T-cell function

Abstract: We investigated whether TCRs restricted to the more ubiquitously expressed MHC class I molecules could be used to redirect human regulatory T cells (Tregs). Using a series of HLA-A2-restricted TCRs that recognize the same peptide-MHC class I complex (pMHC) with affinities varying up to 3500 fold, we observed that TCR affinity had no effect on the ability of the introduced TCRs to confer potent Ag-specific suppressive activity. Surprisingly, we found a naturally occurring, low-affinity MHC class I-restricted TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 48 publications
(69 reference statements)
2
40
0
1
Order By: Relevance
“…16,17 Recently, the generation of antigenspecific human Tregs via viral transduction of a tumor-associated antigen-specific TCR was reported. 9,11,18 These results indicated that transduction of specific TCR could render Tregs antigen specific (monoclonal) and able to suppress immune responses to specific antigens. In these earlier studies, however, functional stability of the Tregs was not clearly addressed.…”
Section: Introductionmentioning
confidence: 91%
“…16,17 Recently, the generation of antigenspecific human Tregs via viral transduction of a tumor-associated antigen-specific TCR was reported. 9,11,18 These results indicated that transduction of specific TCR could render Tregs antigen specific (monoclonal) and able to suppress immune responses to specific antigens. In these earlier studies, however, functional stability of the Tregs was not clearly addressed.…”
Section: Introductionmentioning
confidence: 91%
“…This result suggests that LYP-mediated dampening of TCR activation preferentially impairs effector T cells and tilts the balance toward regulation. It has been reported that Tregs can be activated to suppress by low affinity ligands whereas activation of effector function in Tconv cells requires higher affinity engagement with antigens [50]. Strikingly, the differential requirement can be three orders in magnitude.…”
Section: Ptpn22mentioning
confidence: 86%
“…antigen[specific) suppression) in) Tregs) transfected) with) a) high) affinity) HIV[ specific)TCR)and)a)lower)affinity)tumor)antigen[specific)TCR [22]. )However,)it) should) be) noted) that) the) study) was) performed) using) MHC) class) I[restricted)…”
Section: 6# Data#analysis# )unclassified